(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Abdullah UH, Sufardi S, Syafruddin S, Arabia T. 2022. Soil organic carbon of grassland and bush forest on dryland in Aceh Besar District, Indonesia. Biodiversitas 23: 2594-2600. Soil organic carbon (SOC) is one of the important components that can improve soil conditions and maintain agriculture sustainability. This study was conducted to determine the potential of soil organic carbon in grassland and bush forest in Aceh Besar District. We used purposive random sampling by taking soil samples at various depths with five samples for each land type. The parameters of soil bulk density, % carbon soil, the potential of carbon and carbon stock were analyzed. Soil organic carbon (SOC) analysis followed the Walkley and Black method using analytical guidelines from the Indonesian Soil Research Institute. The results showed that land type and soil depth affected bulk density, % carbon soil, the potential of carbon and carbon stock. Land type affected soil organic carbon in which grasslands had a higher soil carbon than bush forests. In total, total soil carbon stock in the bush forest of Aceh Besar District was higher than that in grassland due to the much larger extent of bush forest in the district. Land use management efforts to improve soil SOC need to be carried out and in collaboration with various parties. Thus, it is necessary to maintain the availability of soil carbon stock for sustainable land management, including agriculture.